International relations theory and the politics of European integration : power, security, and community - Kelstrup, Morten; Williams, Michael C. (Michael Charles), 1960- (Routledge, 2000)
International Relations Theory and the Politics of European Integration focuses on the roles of community, power and security, within the European Union. It features contributions from highly respected international scholars, and covers subjects such as:· sovereignty and European integration · the EU and the politics of migration· the internationalisation of military security · the EU as a security actor · money, finance and power · the quest for legitimacy with regards to EU enlargement.